The photothermal effect in MOFs: covalent post-synthetic modification of MOFs mediated by UV-Vis light under solvent-free conditions. Issue 33 (9th April 2018) - Espín, Jordi; Garzón-Tovar, Luis; Boix, Gerard; Imaz, Inhar; Maspoch, Daniel
Abstract : Photothermal effect can be used to perform covalent post-synthetic modifications on metal–organic frameworks under solvent-free conditions. Abstract : Here, we report the covalent post-synthetic modification (CPSM) of MOFs using the photothermal effect. Specifically, we subjected mixtures of a photothermally active MOF and another reagent to irradiation with a UV-Vis lamp. This caused the MOF to heat up, which in turn caused the other reagent to melt and subsequently react with the functional groups on the walls of the MOF pores. We have exploited this dual function of MOFs as both heater and host for CPSMs to achieve rapid formation of amides from the reaction of representative MOFs (UiO-66-NH2 or MIL-101-NH2 -(Al)) with anhydrides under solvent-free conditions. In addition, this approach enables more complex CPSMs in MOFs such as the formation of amides in UiO-66-NH2 by using an aldehyde through a cascade reaction.